2004
DOI: 10.1074/jbc.m306337200
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids and Insulin Control Autophagic Proteolysis through Different Signaling Pathways in Relation to mTOR in Isolated Rat Hepatocytes

Abstract: Autophagy, a major bulk proteolytic pathway, contributes to intracellular protein turnover, together with protein synthesis. Both are subject to dynamic control by amino acids and insulin. The mechanisms of signaling and cross-talk of their physiological anabolic effects remain elusive. Recent studies established that amino acids and insulin induce p70 S6 kinase (p70 S6k ) phosphorylation by mTOR, involved in translational control of protein synthesis. Here, the signaling mechanisms of amino acids and insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(151 citation statements)
references
References 53 publications
5
143
1
2
Order By: Relevance
“…mTOR inhibitors induce apoptosis in some types of tumor cells (Hosoi et al, 1999;Nepomuceno et al, 2003;Majumder et al, 2004;Avellino et al, 2005), whereas they trigger autophagy in other settings (Noda and Ohsumi, 1998;Gutierrez et al, 2004;Kanazawa et al, 2004;Ravikumar et al, 2004) as well as in malignant glioma cells as shown in this study and our previous investigation (Takeuchi et al, 2005). Autophagy is a process by which cells degrade and recycle proteins and intracellular components in response to stress or starvation (Klionsky and Emr, 2000;Levine and Klionsky, 2004;Shintani and Klionsky, 2004).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…mTOR inhibitors induce apoptosis in some types of tumor cells (Hosoi et al, 1999;Nepomuceno et al, 2003;Majumder et al, 2004;Avellino et al, 2005), whereas they trigger autophagy in other settings (Noda and Ohsumi, 1998;Gutierrez et al, 2004;Kanazawa et al, 2004;Ravikumar et al, 2004) as well as in malignant glioma cells as shown in this study and our previous investigation (Takeuchi et al, 2005). Autophagy is a process by which cells degrade and recycle proteins and intracellular components in response to stress or starvation (Klionsky and Emr, 2000;Levine and Klionsky, 2004;Shintani and Klionsky, 2004).…”
Section: Discussionsupporting
confidence: 64%
“…Induction of autophagy in malignant glioma cells by rapamycin Autophagy is detected in a variety of cells treated with rapamycin (Noda and Ohsumi, 1998;Gutierrez et al, 2004;Kanazawa et al, 2004;Ravikumar et al, 2004). We used electron microscopic analysis to determine whether rapamycin induces autophagy in our malignant glioma cells.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, 40 carried out with hepatocytes isolated from rats fed a high-protein diet, rapamycin stimulated autophagy in the presence of insulin alone, but not in the presence of amino acids. As indicated above, in a variety of cell types, including hepatocytes, mTOR has an absolute requirement for amino acids, and is not activated by insulin alone.…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 99%
“…Sufficient amounts of amino acids from endogenous origin must apparently have been present in these studies (also see Beugnet et al 41 ). According to the authors, 40 amino acids use an mTOR-independent pathway which is initiated by binding one or more amino acids, presumably leucine, to an aminoacid receptor protein in the plasma membrane, which then somehow leads to an inhibition of autophagy that is independent of mTOR. Although a separate signaling pathway starting at the plasma membrane cannot be excluded, the available evidence indicates that mTOR-dependent signaling is stimulated by intracellular amino acids, rather than extracellular amino acids (leucine in particular).…”
Section: Inhibition Of Autophagy By Amino Acidsmentioning
confidence: 99%
“…Numerous pharmacological agents have been reported to stimulate autophagy in an mTOR-independent manner (Sarkar et al, 2007;Zhang et al, 2007), with some involvement of Ca 2 þ and inositol 1,4,5-trisphosphate signaling (Williams et al, 2008). Amino-acid regulation of autophagy also occurs in an mTOR-independent manner in muscle cells (Mordier et al, 2000) through FoxO3-mediated transcription of the autophagy genes MAP1LC3B (microtubule-associated protein 1 light chain 3 b) and BNIP3 (BCL2/ adenovirus E1B 19 kDa protein-interacting protein 3) (Mammucari et al, 2007), and in liver cells (Kanazawa et al, 2004). A small interfering RNA screen for autophagy modulators also identified a number of growth factors and cytokines that suppress autophagy independently of mTOR through inhibition of class-III PI3K (Lipinski et al, 2010).…”
Section: Physiological Control Of Autophagy: Mtormentioning
confidence: 99%